The Principle of Justice and Its Relevance to The Position of The Debtor in The Execution of Fiduciary Guarantees - Yulia Vera Momuat; Ronny A. Maramis; Wulanmas A. P. G. Frederik; Merry E. Kalalo (AIBPM Publisher, 2023)
In a contractual relationship, justice means assuring equality in the rights and obligations of parties in an agreement. This study analyzes the nature of justice regarding the position of debtors and creditors in a fiduciary guarantee agreement. The research method used for this study is the normative legal research method. The results of the study show that the nature of justice is important in a fiduciary guarantee agreement, particularly for the fair treatment of debtors and creditors. Justice must be appropriately applied to not harm the debtor and violate their rights. However, creditors also have a right to security over the credit provided; therefore, justice must be applied proportionally and transparently during each stage of the execution of fiduciary security. Due to this, it is important to determine the requirements and consequences of a breach of the debtor's obligations. Additionally, the principle of justice is also related to recognizing the debtor's rights to defend their interests and maintaining a balance between the rights of the debtor and the creditor. In conclusion, justice is an important principle in ensuring the execution of fiduciary guarantee agreements fairly and avoiding abuse or injustice in the process